Biomaterial-induced conversion of quiescent cardiomyocytes into pacemaker cells in rats - Hu, Yu-Feng; Lee, An-Sheng; Chang, Shih-Lin; Lin, Shien-Fong; Weng, Ching-Hui; Lo, Hsin-Yu; Chou, Pei-Chun; Tsai, Yung-Nan; Sung, Yen-Ling; Chen, Chien-Chang; Yang, Ruey-Bing; Lin, Yuh-Charn; et al. (Nature biomedical engineering, 2022)
Pacemaker cells can be differentiated from stem cells or transdifferentiated from quiescent mature cardiac cells via genetic manipulation. Here we show that the exposure of rat quiescent ventricular cardiomyocytes to a silk-fibroin hydrogel activates the direct conversion of the quiescent cardiomyocytes to pacemaker cardiomyocytes by inducing the ectopic expression of the vascular endothelial cell-adhesion glycoprotein cadherin. The silk-fibroin-induced pacemaker cells exhibited functional and morphological features of genuine sinoatrial-node cardiomyocytes in vitro, and pacemaker cells generated via the injection of silk fibroin in the left ventricles of rats functioned as a surrogate in situ sinoatrial node. Biomaterials with suitable surface structure, mechanics and biochemistry could facilitate the scalable production of biological pacemakers for human use. A silk-fibroin hydrogel converts rat quiescent ventricular cardiomyocytes into pacemaker cardiomyocytes by inducing the ectopic expression of the vascular endothelial cell-adhesion glycoprotein cadherin.